1987
DOI: 10.1073/pnas.84.19.6859
|View full text |Cite
|
Sign up to set email alerts
|

An IgE-binding protein with a distinctive repetitive sequence and homology with an IgG receptor.

Abstract: Proteins that bind IgE play important roles in both the synthesis and function of IgE and are therefore intimately involved in IgE-mediated human allergic disorders. This report describes the structure of an IgE-binding protein, as predicted from sequencing a cDNA cloned from rat basophilic leukemia cells. This protein contains two domains: the amino-terminal domain (140 amino acids) consists of a highly conserved repetitive amino acid sequence, Tyr-Pro-GlyPro/Gln-Ala/Thr-Pro/Ala-Pro-Gly-Ala, whereas the carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 43 publications
3
61
0
2
Order By: Relevance
“…RL-14.5 also exhibits structural similarities with a larger (-30-35 kDa) lactose-binding lectin of mouse termed CBP-35 (Jia and Wang, 1988) and with a rat IgE binding protein (Albrandt et al, 1987), which is probably the rat homolog of CBP-35 (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…RL-14.5 also exhibits structural similarities with a larger (-30-35 kDa) lactose-binding lectin of mouse termed CBP-35 (Jia and Wang, 1988) and with a rat IgE binding protein (Albrandt et al, 1987), which is probably the rat homolog of CBP-35 (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Galectin-3 has been shown to localize to the surface of some cells, for example activated peritoneal macrophages (Sato and Hughes, 1994) (galectin-3 was originally known as the macrophage differentiation marker, Mac-2). Analysis of protein localisation in different cell lines has shown that despite the lack of signal sequence (Albrandt et al, 1987;Cherayil et al, 1989;Oda et al, 1991), galectin-3 is secreted through a pathway independent of the endoplasmic reticulum-Golgi complex Sato et al, 1993). Interestingly, it has also been proposed that distribution of galectin-3 might be regulated by its state of phosphorylation (Huflejt et al, 1993).…”
Section: Other Sites Of Expressionmentioning
confidence: 99%
“…Interestingly, galectin-3 does not comprise two CRDs nor does it form dimers in solution (20,21). Rather, galectin-3 is composed of a N-terminal, non-lectin domain consisting of multiple repeats of a peptide sequence rich in proline, glycine, and tyrosine in addition to its C-terminal CRD (22)(23)(24). Others and our previous study have underlined the importance of the two domains of galectin-3 for its biological functions through the demonstration that both the C-terminal CRD domain and the N-terminal non-lectin domain are essential for its role in signal transduction, cellular adhesion, and lattice formation (Refs.…”
mentioning
confidence: 99%